Managing natural and cultural heritage for a durable tourism - (:unkn) unknown (My University, 2024)
This contributed volume offers a wealth of cases that explore the factors and conditions required for heritage tourism to be economically and socially beneficial to local communities without impairing the natural environment, cultural heritage preservation, or sustainability for future generations. The studies presented here comprise an examination of measures which have been and can be implemented to ensure sustainable use of natural and cultural systems, leading to a new concept of tourism that incorporates science and community practices together to create a favorable environment where tourists and locals can experience meaningful interactions and experiences. The book focuses on the role of stakeholders in the development of a new policy regarding the sustainable management of cultural tourism and the possibility of their involvement in the processes governing policy-making. Emphasis is placed on the role and commitment of local and international authorities, including UNESCO, in preserving the world's endangered cultural and natural heritage, as well as the responsibilities of Member States and public and private actors with respect to future conservation challenges.
Keywords: Cultural heritage; Cultural tourism; Sustainable tourism; UNESCO sites; Governance; Local governments; Tourism destinations